Synthesis, physic and chemical properties of 2-(4-R-5-(thiophene-2-ylmethyl)-4h-1,2,4-triazole-3-ylthio)acetate acids and their salts - O. A. Suhak; О. I. Panasenko; Ye. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Derivatives of 1,2,4-triazole are inherent in various types of biological activity. They can be used as pesticide and medicinal drugs (anticonvulsants, analgetics, antitumor and antibacterial). In this regard the search of new methods of synthesis and investigation of biological activity of 2-(4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-ylthio)acetate acids and their salts is relevant nowadays. With the aim of finding the new biologically active compounds 2-(4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-ylthio)acetate acids and their salts are synthesized, where R is methyl, ethyl, phenyl. The interaction of 4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thions with monochloracetate acid in the medium of i-propyl alcohol in the presence of an equivalent amount of alkali the corresponding 2-(4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4 triazole-3-ylthio)acetate acids are obtained on the basis of which the corresponding salts of morpholine, dimethylamine, monoethanolamine, pteridine, ZnSO4 , CuSO4, NaOH and KOH are obtained and the structure of the received compounds was confirmed on the basis of the data of elemental, IR-, 1H-NMR-spectroscopy. The synthesis of 2-(4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-ylthio) acetate acids and their salts was conducted. With the help of modern physico-chemical methods: elemental analysis, IR, 1H-NMR-spectroscopy the structure of synthesized compounds, and their individuality by HPLC-MS is proved. In the IR spectrum of the compound 2-(4-phenyl-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-ylthio)acetate acid Ic available band fluctuations groups characteristic for the nucleus of 1,2,4-triazole: NH- in the range of 3 400-3 100 cm-1,-C=N- - 1 690-1 620 cm-1. Also present band fluctuations groups -C-S- at 691 cm-1. Available band fluctuations characteristic of the group -CH2 within 1496.59 cm-1 and group -COO-H- - 1722.70 cm-1. This suggests the possibility to further study the biological action of the synthesized compounds.